Education helps to achieve shared prosperity: evidence from China - Wang, Xingyu; Ruan, Jing (Frontiers in Education, 2024)
Abstract：With the elimination of absolute poverty in China, the realization of the common wealth of all people has become the theme of the new era, and how to effectively promote the process of realizing the common wealth has become an important issue that needs to be resolved urgently.Combined with the essential connotation of common wealth, this paper argues that "it is better to teach a man to fish than to teach him to fish", and education plays an important role in improving the quality of nationals and promoting the common wealth in a solid manner. Therefore, this paper focuses on the realization path of education for common prosperity. In order to explore this issue, this paper has constructed the index of education development level and the coefficient of common wealth, which characterize the independent variable and the dependent variable respectively. At the same time, it empirically analyses the mechanism of education development level on common prosperity by using two-way fixed effect model. It is found that, firstly, from 2012 to 2020, the coefficient of common wealth in China shows an increasing trend, and it is higher in the eastern region than in other regions, and lowest in the western region; secondly, educational inequality hinders common wealth to a certain extent; thirdly, the average years of education of China's current employed population is low, which may have a negative impact on the common wealth; and fourthly, improving the level of education can significantly contribute to the realization of common wealth.